Vestibular function after cochlear implantation: A test battery and case‐by‐case approach. Issue 3 (4th June 2020) - Piker, Erin G.; Riska, Kristal; Garrison, Doug; Kaylie, David M.
Abstract: Objectives: The purpose of this study was to assess the effects of cochlear implantation on the functional integrity of the horizontal semicircular canal using multiple methodologies, and to discuss and highlight the limitations of using isolated vestibular tests to assess vestibular function in surgical ears. Methods: Ten cochlear implant patients were consented to undergo a preoperative and 3‐month postoperative vestibular assessment. The horizontal semicircular canal (SCC) was assessed using three different vestibular test measures that assess function using different stimuli and at different frequencies ranges: caloric testing, sinusoidal harmonic acceleration testing in the rotary chair, and video head impulse testing in the plane of the horizontal SCC. Data was analyzed using different methods: descriptive, statistical, and by an examination of individual case studies. Results: Each analysis method yielded a different interpretation. Statistical analysis showed no significant group mean differences between baseline pre‐op vestibular test results and 3‐month post‐op vestibular test results. Descriptive analysis showed 30% of individuals presented with postoperative abnormal vestibular testing findings. A case study examination showed that only one patient presented with a post‐op decrease in vestibular function in the implanted ear. Conclusions: There are several limitations of conventional vestibular testing in postsurgical cochlear implant patients. A test‐battery approach, including case history, and test interpretation made on a case‐by‐case basis is needed to determine whether the patient has undergone vestibular damage, is at risk for falling, or in need of further management. Level of Evidence: 2b individual cohort study. Abstract : The effects of cochlear implantation on vestibular function are not fully understood as methodologies across studies vary greatly and results between studies are often in disagreement. We assessed the functional integrity of the horizontal semicircular canal pre‐ and post‐cochlear implantation using different test methods and analyzing the data from different approaches. Each analysis method yielded a different interpretation, leading us to conclude that a test‐battery approach and interpretation made on a case‐by‐case basis is needed to determine whether the patient has undergone vestibular damage, is at risk for falling, or in need of further management.